Side-effects in women treated with adjuvant endocrine therapy for breast cancer - L.M. Rademaker; R. Gal; A.M. May; M.C.T. Batenburg; F. van der Leij; R.M. Bijlsma; H.M. Verkooijen; A. Doeksen; M.F. Ernst; D.J. Evers; C.C. van der Pol; E.M. Monninkhof (Breast, 2025)
Many women with breast cancer prematurely discontinue adjuvant endocrine therapy, leading to increased mortality. We performed a cross-sectional survey (n = 456) within the Dutch UMBRELLA-cohort to gain insight into the prevalence of side-effects and its association with premature discontinuation. Almost all current endocrine therapy users experienced side-effects (92.7 %), most frequent were vasomotor- and musculoskeletal symptoms. The most reported reason for premature discontinuation was side-effects (88.1 %). Former treatment with chemotherapy was associated with more reported side-effects (97.2 % vs 82.5 %, ORadj 6.31), but less premature discontinuation of endocrine therapy (18.6 % vs 28.6 %, p-value 0.016).